1970
DOI: 10.1128/jb.101.3.827-835.1970
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Similarities Among Pseudomonas pseudomallei, Pseudomonas multivorans , and Actinobacillus mallei

Abstract: Annealing experiments on membrane filters were carried out with deoxyribonucleic acids (DNA) from selected strains of the nomen-species of Pseudomonas, Actinobacillus, Chromobacteriwn, and Micrococcus, with the use of DNA of Pseudomonas pseudomallei and Actinobacillus mallei as reference materials. Under the usual conditions employed in these experiments, the results were not quantitatively reproducible. Incorporation of dimethylsulfoxide (DMSO) into the incubation medium greatly increased differences in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…B. mallei and B. pseudomallei were separated into two species but nowadays they are considered to be pathovars of only one species due to DNA^DNA hybridisation studies [23,37]. But only few genes have been compared so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. mallei and B. pseudomallei were separated into two species but nowadays they are considered to be pathovars of only one species due to DNA^DNA hybridisation studies [23,37]. But only few genes have been compared so far.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was of no surprise that DNA^DNA homology studies revealed that both species are simply pathovars of one single species. However, the nomenclature remained unchanged [23,37]. Recently, it was noted that in the entity of the soil isolates of B. pseudomallei various apathogenic, arabinose-fermenting strains exist [5,25,29,33,36].…”
Section: Introductionmentioning
confidence: 99%
“…Burkholderia pseudomallei is a saprophytic organism that routinely can be isolated from environmental niches like water, moist soil and rice paddies (Brook et al, 1997). These two species were shown to represent a single genomic species by DNA-DNA hybridization criteria (Rogul et al, 1970). However, the major differences in their biochemical activities and in the clinical symptoms and epidemiology justify this two-species concept.…”
Section: Diversity Of the Genus Burkholderiamentioning
confidence: 99%
“…This has been demonstrated in part by comparing their cellular lipid and fatty acid compositions (Rogul et al . ; Yabuuchi et al . ; Godoy et al .…”
Section: Introductionmentioning
confidence: 99%